2021
DOI: 10.1017/s1368980021002895
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and the double burden of malnutrition in Colombian rural households

Abstract: Objective: This study aimed to examine in Colombian rural households the association between different severity levels of household food insecurity and the presence of the double burden of malnutrition (SCOWT), defined as the coexistence of a stunted child under five years and an overweight or obese (OWOB) mother. Design: A secondary data analysis was conducted using cross-sectional data from the Colombian National Nutritional Survey (ENSIN) 2015. Household food insecurity status was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 170 publications
1
7
1
2
Order By: Relevance
“…Another study conducted by Sims et al found that there was FI and malnutrition among Indian rural women ( 137 ). In addition, Sansón-Rosas et al found high rates of FI in Colombian rural households ( 138 ). It is accepted that poverty is significantly linked to FI ( 139 ) and it is often considered the most common determinant of FI across the globe ( 139 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Sims et al found that there was FI and malnutrition among Indian rural women ( 137 ). In addition, Sansón-Rosas et al found high rates of FI in Colombian rural households ( 138 ). It is accepted that poverty is significantly linked to FI ( 139 ) and it is often considered the most common determinant of FI across the globe ( 139 ).…”
Section: Discussionmentioning
confidence: 99%
“…While Forero [15] explains that residence in rural areas doubles the prevalence of chronic malnutrition and developmental delay compared to urban areas, being 4.7% compared to 2.9%. In accordance with the first approach, Agudelo [3] agrees that at least half of the nutritional alterations occur in rural areas, while Sanson-Rosas et al [8] show in their study that in rural areas there is a greater coexistence of overweight mothers and malnourished children, exceeding the national prevalence [16]. In the study by Neufeld et.al.…”
Section: Resultsmentioning
confidence: 82%
“…Among the associated factors, it has been possible to identify that the level of maternal education, underdevelopment, displacement conditions, food insecurity are risk factors for child malnutrition [7]. Despite the fact that rural areas are where food is produced, they are the ones that are most food insecure [8]. Another important factor when talking about child malnutrition in the Colombian context is the presence of ethnic communities, which live in regions far from each other and far from health care centers; In these communities, multiparity increases the risk of forced weaning, competition for nutrition and inadequate complementary feeding, accumulating factors that influence food insecurity in the region [9][10][11].…”
Section: Malnutrition Due To Micronutrient Deficiency: Includes Defic...mentioning
confidence: 99%
“…Rumah tangga yang tidak tahan pangan berisiko terjadi peningkatan asupan pangan yang padat kandungan energi dan rendahnya kualitas makanan yang ditandai dengan rendahnya variasi pangan. Selain itu juga, ketidaktahanan pangan di rumah tangga berdampak pada ketidakseimbangan distribusi pangan antar anggota keluarga yang disebabkan oleh keterbatasan akses dan jumlah pangan di rumah tangga (5,20). Sehingga wanita yang mengalami ketidaktahanan pangan berisiko mengalami kelebihan berat badan yang lebih tinggi.…”
Section: Pembahasanunclassified